DOP18 Advanced optical diagnosis technology for assessment of endoscopic and histological remission in Ulcerative Colitis: A systematic review and meta-analysis. (21st January 2022) - Nardone, O M; Snir, Y; Hodson, J; Cannatelli, R; Labarile, N; Siau, K; Hassan, C; Yanai, H; Dotan, I; Ghosh, S; Iacucci, M
Abstract: Background: Advanced endoscopic technologies led to significant progress in the definition of endoscopic remission of ulcerative colitis (UC), and correlate better with histological changes, compared to standard endoscopy. However, whilst studies have assessed the diagnostic accuracy of endoscope technologies individually, there is current limited data comparing between technologies. As such, we aimed to compare the correlations between endoscopy and histology disease activity scores across endoscope technologies Methods: We searched PubMed and Embase in January 2021 for eligible studies reporting the correlation between endoscopy and histology activity scores in UC. Studies were grouped by endoscope technology as standard-definition white light (SD-WLE), high-definition white light (HD-WLE), or electronic virtual chromoendoscopy (VCE), and comparisons made between these groups Results: A total of N=27 studies were identified, of which N=12 were included in a meta-analysis of correlations between endoscopic and histological activity scores. Combining these returned a pooled correlation coefficient (rho) for the SD-WLE group of 0.61, which did not differ significantly from HD-WLE (rho: 0.79, p=0.140) or VCE (rho: 0.70, p=0.471) [Fig 1a]. In addition, N=4 studies reported the accuracy of endoscopic activity scores on WLE and VCE to diagnose histological remission. Pooling these found significantly higher accuracy for VCE, compared to WLE (risk ratio: 1.13, 95% CI: 1.07–1.19, p<0.001).[Fig 1b] Conclusion: Activity scores assessed using endoscopy are strongly correlated with activity on histology. VCE appears to have better accuracy for the diagnosis of histological remission in UC, compared to WLE.